Evolution of shape and size of voids under shear dominated loading conditions in ductile materials. (September 2020) - Kumar, Suranjit; Samal, M.K.; Singh, P.K.; Chattopadhyay, J.
Highlights: Void evolution equations are proposed for porous metal plasticity. It captured the void flattening and reduction in its volume fraction under shearing. The results of the scheme have been validated using 2D and 3D cell model analysis. Abstract: The micromechanism of ductile fracture involves processes of void nucleation, growth, and coalescence. The change of void volume fraction with loading in porous metals affects their stress carrying capability. These changes depend upon the stress triaxiality. Though the voids grow under hydrostatic loading conditions, they tend to distort in shear dominant loading conditions leading sometimes to change in porosity. In addition, the voids change their shape and orientation during the loading process which needs to be captured accurately in a material constitutive model in order to predict the deformation behavior. Many of the existing models in literature do not adequately represent the changes in void volume fraction and their shape for a wide range of values of stress triaxilities. In this work, a scheme has been proposed to evaluate the change of average shape of the ellipsoidal and cylindrical voids consistent with their change in volume fraction with loading for different types of loading conditions including those of shear dominated conditions. The results of the proposed method have been validated with 2D and 3D cell model finite element analysis under pure shear, combined tension-shear, and compression-shear loading conditions.